2016
DOI: 10.1108/ijse-02-2015-0033
|View full text |Cite
|
Sign up to set email alerts
|

Human capital development for SMEs in Pakistan: is the “one-size-fits-all” policy adequate?

Abstract: Purpose – Pakistan adopted “one-size-fits-all” policy for human capital (HC) development with the assumption that the level of HC is equal across industry and firm size. The purpose of this paper is to test this major assumption on which this policy is based, by comparing the differences in the levels of HC, overall and by dimensions of HC, by industry and firm size. Design/methodology/approach – The study is based on new data set of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 40 publications
4
32
1
1
Order By: Relevance
“…Similarly, human capital development is also facing 'one-size-fit for all' approach and is far away from the required attention of government for entrepreneurship development. Current study is confirming the issue highlighted in previous researches on human capital of Pakistan (Mubarik, 2015).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Similarly, human capital development is also facing 'one-size-fit for all' approach and is far away from the required attention of government for entrepreneurship development. Current study is confirming the issue highlighted in previous researches on human capital of Pakistan (Mubarik, 2015).…”
Section: Resultssupporting
confidence: 90%
“…Subsequently, the question on the role of government to policy development was inquired. Since entrepreneurship is different in nature than conventional business and one size fit for all approach was reported which is not suitable for innovation and growth of business (Mubarik, 2015). In our study it was also found that government has doing nothing in aspect of entrepreneurship policy.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…It is precisely through such HC that ambidexterity is able to access and utilize knowledge from multiple domains, discover novel solutions to existing problems, and challenge assumptions behind prevailing knowledge and practices. Effectively managed HC contributes to the incremental and radical innovations ( Mubarik et al., 2016 ; Raisch et al., 2009 ). Asiaei et al.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Untuk itu, diperlukan networking yang luas dan kuat, baik secara internal dan eskternal, maupun vertikal dan horizontal [9]. Disamping itu, agar terbentuknya SDM yang mapan, entrepreneur membutuhkan pengalaman, pendidikan dan pelatihan, kemampuan dan ketrampilan personal, pemenuhan sumber daya, sikap, stabilitas dan kesehatan [10]. Dengan demikian, dalam mengembangkan entrepreneur, diperlukan peran dari perguruan tinggi [11].…”
Section: Pendahuluanunclassified